EVALUASI KESESUAIAN LAHAN TANAMAN KOPI ROBUSTA MENGGUNAKAN FUZZY LOGIC DI KABUPATEN TANAH DATAR - fitri aji; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This research was conducted in Tanah Datar District which aims to determine the suitability of Robusta coffee plantations and the direction of the development of Robusta coffee plant suitability. The method used is a descriptive approach with quantitative research and the data used are secondary data with data processing using fuzzy logic and Boolean logic. The results of this study indicate that the suitability of class Robusta coffee plants is not suitable with an area of ​​6,661 hectares covering X Koto Subdistrict, Sungai Tarab, Pariangan, Sungayang and Lintau Buo Utara. The appropriate class has an area of ​​74,175 Ha. Classes are very suitable covering an area of ​​50,672 hectares including Rambatan, Padang Ganting, Tanjung Emas, Lintau Buo Utara, Lintau Buo and Batipuh. Development directions that are not suitable for robusta coffee are 84,923.58 hectares, Lintau Buo Utara, X Koto, Batipuh Selatan, Tanjung Emas, Pariangan, Sungayang, Sungai Tarab, and Batipuh. The appropriate development direction has an area of ​​46,586.06 Ha, which is dominantly located in Lintau Buo Subdistrict with an area of ​​7,942.44 Ha following the Lintau Buo Utara Subdistrict, 7,149.18 Ha, Rambatan 6,611.04 Ha, Tanjung Emas 4,220.82 Ha and X Koto Subdistrict 3,602.68 Ha.